Pola Komunikasi Dakwah pada Instagram Badan Amil Zakat Nasional Provinsi Jawa Barat dalam Memotivasi Masyarakat Untuk Berzakat, Berinfak dan Bersedekah Pada Periode 2020-2022 - Sarah Aulia Pebrian; Bambang Saiful Ma'arif; Asep Ahmad Siddiq (UNISBA Press, 2023)
Abstract. Nn The da'wah communication pattern is a role contained in the Badan Amil Zakat Nasional Provinsi Jawa Barat program. On that basis, this research focuses on finding out the factors that influence da'wah communication patterns and examines more deeply how da'wah communication patterns are carried out by Badan Amil Zakat Nasional Provinsi Jawa Barat. In this study the researchers focused on